BIOAKTIVITAS ANTIOKSIDAN SENYAWA EKSOPOLISAKARIDA DARI MIKROALGA Dunaliella sp. - Diah Astika Winahyu (Fakultas MIPA Universitas Tulang Bawang Lampung, 2017)
A study of antioxidant compounds in microalgae, Dunaliella sp. In Conway / Walne media. Microscope observation with magnification 400 times obtained diameter Dunaliella sp. Sebebsar 6.42 μm. Preliminary results of antioxidant activity using DPPH reagent showed Dunaliella sp. Excreting antioxidant compounds. The extract obtained by extracting antioxidant compounds exopolysaccharide compounds from the filtrate with the addition of 70% ethanol and then centrifuged and freeze-dried by the method of FTIR spectrum data dry. Unidentified exopolysaccharide compounds containing uptake helping O - H in the area of 3544.82 cm-1, C - H in area of 2828.59 cm-1, helping the C • O at 1624.24 cm-1 region, CH2 bending at 1419.44 cm-1 region, and helping C - O at 1151.88 cm-1 region. Furthermore, quantitative test results of antioxidant compounds that have a value of 4.279%. So it is concluded that the exopolisakarida compound from Dunaliella sp. Is a potential source of antioxidant compounds. Keywords : Antioxidant, exopolisaccharide, Dunaliella sp.